1990
DOI: 10.1203/00006450-199004000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Hematologic Effects and Immune Complex Formation Related to Pertussis Immunization

Abstract: ABSTRACT. Selected metabolic, hematologic, and immunologic functions were evaluated in 3-to 6-mo-old Finish infants who received whole-cell pertussis-component diphtheria and tetanus toxoids and pertussis vaccine, adsorbed (DTP) vaccine, and in 4-to 6-y-old Los Angeles children who received either a licensed DTP va-ccine or an acellular pertussis component DTP vaccine. One d after immunization, there was an increase in total leukocytes and neutrophils and a decrease in lymphocytes in all vaccinees. In 4-to 6-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…It is therefore possible that white cell count changes post-primary immunization would be at least as marked, if not more, in other populations. Previous studies conducted in white European and mixed American populations have also shown white cell count increases at one-day post-immunization [5] , [9] , though to a lesser extent than with the combination of vaccines used in this study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is therefore possible that white cell count changes post-primary immunization would be at least as marked, if not more, in other populations. Previous studies conducted in white European and mixed American populations have also shown white cell count increases at one-day post-immunization [5] , [9] , though to a lesser extent than with the combination of vaccines used in this study.…”
Section: Discussionsupporting
confidence: 57%
“…However, the effect on white cell counts of the co-administration of multiple vaccine antigens, such as those received during primary immunizations, is unknown. Studies conducted in the 1980s in Finland and the USA in a small number of older infants, showed an increase in white cell counts post administration of the combined Diptheria-Tetanus-whole cell Pertussis (DTwP) vaccination [5] . However, few similar studies have been published looking at younger infants and using the enhanced combination of vaccine antigens currently in use.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the ratio of the increment of the plasma insulin level to that of blood glucose at 30 min after the glucose challenge remained significantly greater 4, 30, and 60 days after the initial intravenous PT injection compared with the baseline glucose tolerance test response. Infants vaccinated with DTP vaccines have also been noted to have an increase in serum insulin levels (319,552). Neonates with severe pertussis are occasionally found to be markedly hypoglycemic, suggesting hyperinsulinemia (156,165,360).…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…In comparison to the values measured in control group, all vaccinated groups with or without addition of adjuvants in this study demonstrated a significant increase in TLC indicated by the marked neutrophilia, lymphocytosis and monocytosis with the highest increase was observed when horses were injected with a combination of toxoid and toxin and provided with CFA (Sahal et al, 2004). These effects were suggested to be due to the release of the biologically active lymphocytosis promoting factor (LPF) which was thought to be the major responsible for the large increase in leukocyte, neutrophil, and lymphocyte counts (Mink et al, 1990).Further, vaccine is known to behave as mitogens or superantigens on some lymphocyte subpopulations leading to lymphocyte proliferation and this is likely a factor in the immunological activation following vaccination (Monaco et al, 2019 andArfuso et al, 2021). Arfuso et al, (2021) added that following vaccination, several leukocyte populations, such as lymphocytes, monocytes, and neutrophils, changed which likely reflected the animals' systemic immune-biological adaptation to the vaccine, and in particular to the second dosage of injection.…”
Section: Discussionmentioning
confidence: 99%